Guidelines for safe extubation and respiratory rehabilitation in the intensive care unit - Saeed Alqahtani, Khalid; Alshamrani, Rakan Ali; Alanazi, Saud Olayan; AlJarbou, Ahmed Saad; Alharthi, Faris Saeed; Alzahrani, Moath Moeed; Alromaihi, Ayedh Jabr; Alhamid, Omar Abdulaziz; Alamri, Mohammed Abdullah; Alqahtani, Abdulmajeed Essa; Alshehri, Turki Atef; Alanazi, Khalid Saud; et al. (International Journal Of Community Medicine And Public Health, 2024)
Safe extubation and effective respiratory rehabilitation are pivotal in the recovery of critically ill patients in the intensive care unit (ICU). Extubation readiness is determined by assessing respiratory function, airway patency, neurological status, and hemodynamic stability. Tools such as spontaneous breathing trials (SBTs) and the cuff leak test provide valuable insights, while neurological and hemodynamic evaluations further guide decision-making. Ensuring the resolution of the primary illness is critical to minimize the risk of extubation failure and its associated complications. The process of extubation involves meticulous preparation and technique to ensure a smooth transition from mechanical ventilation. Pre-extubation interventions, including secretion management and corticosteroid administration for high-risk patients, are vital. Techniques like gradual cuff deflation and tube removal during peak inspiration, coupled with positioning strategies, reduce complications such as aspiration and airway obstruction. Post-extubation respiratory support, including high-flow nasal cannula (HFNC) and non-invasive ventilation (NIV), plays a crucial role in stabilizing high-risk patients and preventing reintubation. Rehabilitation strategies focus on early mobilization, inspiratory muscle training, and pulmonary physiotherapy to enhance recovery and prevent long-term sequelae. Nutritional optimization is emphasized to counteract muscle weakness and promote tissue repair. Continuous monitoring for respiratory distress and addressing psychological impacts, such as post-intensive care syndrome (PICS), are integral to comprehensive care. Evidence-based protocols, individualized care plans, and multidisciplinary collaboration are essential to improving patient outcomes and reducing ICU-related morbidity and mortality.